Tingkat sosial ekonomi, tinggi badan orang tua dan panjang badan lahir dengan tinggi badan anak baru masuk sekolah - Norliani Toto Sudargo dan R. Dwi Budiningsari (Berita Kedokteran Masyarakat (BKM), 2005)
Background: Stunting among children starting primary school is highly prevalent in Central Kalimantan. It shows 50,54%. This condition is obviously showed by their short statures which are below the national average. Male is 108,6cm and female is 107,7cm while the national average shows 114,9cm for male and 114,0cm for female. Mainly in Palangkaraya, children's height is increasing in every measurement, but yet those are still below the national average. Objectives: The objectives of this research was to study the correlation of socio-economic factor, parent's height, and length at birth with height of children starting primary school in Palangkaraya, Central Kalimantan. Methods: This was an observational study with case control design. Subjects were 96 stunted children as cases and 192 non stunted children as control. The age is between 5 – 7 years old. Research was based on socio-economic performance (income and education), height of children starting primary school, length at birth, and parent's height. The data were analyzed to know the association between each factors among and stunting in children. Results : Chi-square test showed there was significant correlation